2014
DOI: 10.3109/08916934.2014.929667
|View full text |Cite
|
Sign up to set email alerts
|

The emerging role of circulating microRNAs as biomarkers in autoimmune diseases

Abstract: The highly conserved RNAs known as microRNAs (miRNAs) are a class of small, single-stranded, non-coding RNAs that play a critical role in the regulation of host genome expression at the posttranscriptional level. MiRNA-mediated gene regulation is vital for normal cellular functions, such as the cell differentiation, proliferation and apoptosis, and nearly one-third of human messenger RNAs might be miRNA targets. Increasing evidence has suggested that miRNAs play a critical role in the regulating the immune sys… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
42
0
2

Year Published

2015
2015
2020
2020

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 63 publications
(46 citation statements)
references
References 103 publications
2
42
0
2
Order By: Relevance
“…24,25 Their stability, along with the development of sensitive methods for their detection and quantification, 20 makes circulating miRNAs as ideal candidates for biomarkers. Investigators have identified changes in circulating miRNAs in a number of disease processes (reviewed in references 2628) and we previously reported changes in circulating plasma miRNAs in patients with MS. 29 In the present study, we investigated serum miRNAs in MS as part of the NIH common fund UH2 initiative. We found that several serum miRNAs are differentially expressed in MS, associate with disease stage, and correlate with disability.…”
mentioning
confidence: 91%
“…24,25 Their stability, along with the development of sensitive methods for their detection and quantification, 20 makes circulating miRNAs as ideal candidates for biomarkers. Investigators have identified changes in circulating miRNAs in a number of disease processes (reviewed in references 2628) and we previously reported changes in circulating plasma miRNAs in patients with MS. 29 In the present study, we investigated serum miRNAs in MS as part of the NIH common fund UH2 initiative. We found that several serum miRNAs are differentially expressed in MS, associate with disease stage, and correlate with disability.…”
mentioning
confidence: 91%
“…MiRNAs are important regulators of both genes and pathways of immune cells including proliferation, differentiation, and apoptosis [30]. Furthermore, dysregulated miRNA expression is associated with autoimmunity and inflammation [31,32].…”
Section: Epigenetic Mechanismsmentioning
confidence: 99%
“…In latent EBV infections involving host functional immunity, EBV expresses limited levels of protein but high levels of noncoding RNAs, including miRNAs. This indicates that the miRNAs are related to viral immune evasion (Jia et al, 2014;Zeng et al, 2014). EBV expresses about 40 mature miRNAs that target viral or cellular genes to induce different functions.…”
Section: Introductionmentioning
confidence: 99%